EARLY DETECTION AND TREATMENT OF CHRONIC OBSTRUCTIVE PULMONARY DISEASE - Djabbarova Akida Mannapovna; Abdulatipov Akramjon G'ulomjon ogli; Atoev Javokhir Avaz Ali (Scholar Express Journals, 2023)
The article covers significant points of early detection and treatment of chronic obstructive pulmonary disease. In addition, basic symptoms of the illness were analyzed deeply.
Keywords: COPD; symptom; preventable; emphysema